Knowledge, attitude and practices regarding financial markets and management among the healthcare professionals - Khan, Hafiza; Hugar, Shivayogi M.; Kohli, Neha (International Journal Of Community Medicine And Public Health, 2023)
Background: The aim of the study was to assess the levels of knowledge, attitude and practices regarding the financial markets and financial management prevailing among the healthcare professionals. Methods: A cross-sectional study was conducted among 328 participants from health care profession which included different specialisations like Ayurveda, Homeopathy, Dental, Physiotherapy, Nursing and MBBS. A set of questionnaire divided into demographic data, knowledge, attitude and practices consisting of 17 questions was distributed among the participants. Software used for this descriptive analysis was IBM SPSS software (version 20.0 Chicago IL, USA). Results: Our study showed that the participants were more financially knowledgeable and had a positive attitude with older age and the participants from the Ayurveda had very poor financial knowledge and attitude. The correlation between Knowledge, Attitude and Practice was found to be highly statistically significant (‘p’=0.0001). Conclusions: The participants with older age had good levels of knowledge, practices and attitude but the younger participants had to be more educated regarding the importance of investments in the tools of financial markets and the importance of managing their finances to gain financial freedom must also be taught. Overall, financial literacy is supposed to be provided among healthcare professionals.